Academic Validation Culture in Social Media: Educational Management Challenges Against the Digital Achievement Mentality - Risza Presty Rumani (Gestion Educativa, 2026)
The pervasive integration of social media into academic environments has catalyzed the emergence of Academic Validation Culture (AVC), a phenomenon in which students increasingly evaluate their academic worth, identity, and motivation through the lens of digital recognition, approval, and comparative performance metrics. This systematic literature review investigates the nature, drivers, and consequences of AVC within higher education, with particular emphasis on its implications for educational management in the era of digital achievement mentality. Drawing on 20 peer-reviewed studies published between 2020 and 2026, this review synthesizes evidence on how social media-mediated validation-seeking behavior intersects with academic performance, psychological well-being, self-efficacy, and institutional governance. Findings reveal that AVC is reinforced by algorithmic feedback loops, peer comparison dynamics, and the gamification of academic milestones on digital platforms. Students immersed in AVC contexts demonstrate heightened anxiety, reduced intrinsic motivation, unstable self-concept, and greater susceptibility to academic procrastination. Educational management systems have largely failed to address AVC as a distinct institutional risk, relying instead on generic digital literacy interventions insufficient for the complexity of this challenge. This review proposes the Academic Digital Wellness Governance Framework (ADWGF), a four-component model comprising: (1) institutional AVC awareness policy, (2) pedagogical redesign toward process-oriented assessment, (3) digital citizenship education, and (4) integrated psychological support systems. The framework offers educational leaders, curriculum designers, and policymakers a structured, evidence-based pathway toward healthier digital academic cultures.